2022
DOI: 10.3390/ma15207092
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Friction and Wear Characteristics of Wire Rope Contact with Sheave under Long-Distance Transmission Conditions

Abstract: Wire rope has different degrees of surface wear under long-distance transmission conditions, which leads to performance degradation and greatly threatens its safety and reliability in service. In this paper, friction and wear tests between the transmission wire rope and sheave under different sliding velocities (from 0.8 m/s to 1.6 m/s) were carried out using a homemade test rig. The material of the steel wires was low carbon steel, and pulley material was ASTM A36 steel plate. The sliding friction coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Goto and Amamoto's experiments revealed the transition from mild to severe wear and "quasi-mild wear" [19]. Xiangdong et al observed the inverse relationship between friction coefficient and sliding distance and the evolution of wear debris [20].…”
Section: Wear Models For Sheavesmentioning
confidence: 99%
“…Goto and Amamoto's experiments revealed the transition from mild to severe wear and "quasi-mild wear" [19]. Xiangdong et al observed the inverse relationship between friction coefficient and sliding distance and the evolution of wear debris [20].…”
Section: Wear Models For Sheavesmentioning
confidence: 99%